Synchrony of visual perception induced by voice vibration - Marlin Spike Werner (Journal of All India Institute of Speech and Hearing, 1970)
Under special conditions, the voice can be used to drive the visual preceptual system in synchrony with the voice's fundamental frequency. The phenomenon has been demonstrated on a number of moving objects and has been calibrated at frequencies ranging from 60 to 324 Hz. Implications for fatigue in machine operators, altered mental states, and a commercial application are discussed.